Impaired expression of innate immunity-related genes in IgG4-related disease: A possible mechanism in the pathogenesis of IgG4-RD. Issue 3 (3rd May 2020) - Nakamura, Takuji; Satoh-Nakamura, Tomomi; Nakajima, Akio; Kawanami, Takafumi; Sakai, Tomoyuki; Fujita, Yoshimasa; Iwao, Haruka; Miki, Miyuki; Masaki, Yasufumi; Okazaki, Toshiro; Ishigaki, Yasuhito; Kawano, Mitsuhiro; et al.
Abstract: Background: IgG4-related disease (IgG4-RD) is characterized by elevated serum IgG4 and tissue infiltration by IgG4-positive plasma cells. The pathogenesis of this disease is not clear. Transcriptome analysis was performed to identify genes over- and under-expressed in patients with IgG4-RD. Method: DNA microarray analysis was performed using RNA from peripheral blood mononuclear cells of two patients with IgG4-RD and four healthy individuals. Genes showing a greater than threefold change in expression in IgG4-RD patients following steroid therapy were identified. Four genes related to innate immunity such as transcobalamin I (TCN1), secretory leukocyte peptidase inhibitor (SLPI), bactericidal/permeability-increasing protein (BPI) and lactotransferrin (LTF) were assessed by real-time PCR in 15 IgG4-RD patients and 13 healthy individuals. Result: DNA microarray analysis identified 30 genes showing a greater than threefold change in expression in IgG4-RD patients following steroid therapy. Real-time RT-PCR showed that the levels of mRNAs encoding TCNI and SLPI, except for BPI and LTF, were significantly lower in patients with IgG4-RD than in healthy people. The levels of all four mRNAs in patients with IgG4-RD were significantly increased after steroid treatment. Conclusion: These results indicate that reduction in expression of innate immunity-related genes may participate in the pathogenesis of IgG4-RD that steroid treatment may rectify impaired innate immunity as well as acquired immunity.